2019
DOI: 10.1136/bmjgast-2018-000254
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the combined effect of factors influencing bowel preparation and adenoma detection rates in patients undergoing colonoscopy

Abstract: BackgroundColonoscopy is a commonly used modality for screening and surveillance of colorectal cancer (CRC). Therefore, it is essential to have adequate bowel preparation (prep) for the procedure which depends on type of bowel regimens, diet before colonoscopy and timing of the procedure.AimsThe purpose of this study is to analyse the effect of multiple factors on adenoma detection rate (ADR) and prep quality of colonoscopy. This is the also the first study determining outcomes based on various combinations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Several studies suggest that the success of bowel preparation is influenced by a number of factors, such as the bowel preparation selected, the dosing regimen used, the time between completion of the preparation, and the procedure and patient education (e. g., telephone re-education the day before a colonoscopy) 10 11 12 13 14 15 . Despite advances in this area, inadequate preparation remains a problem during colonoscopies 7 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that the success of bowel preparation is influenced by a number of factors, such as the bowel preparation selected, the dosing regimen used, the time between completion of the preparation, and the procedure and patient education (e. g., telephone re-education the day before a colonoscopy) 10 11 12 13 14 15 . Despite advances in this area, inadequate preparation remains a problem during colonoscopies 7 8 .…”
Section: Introductionmentioning
confidence: 99%
“…First, only RCTs published in English were included, which resulted in an English language bias and made it easier to yield the expected conclusion. However, none of the 16 included studies or other related literature ( Tariq et al, 2019 ) reported that the quality of bowel preparation with the CLD was superior to that with the LRD, suggesting that we should not strongly consider the effects of this bias. Second, different studies adopted different schemes so that patients could use the LRD.…”
Section: Discussionmentioning
confidence: 98%
“…Poor bowel preparation leads to missed adenomas, repeat examinations, patient discomfort, and higher healthcare cost. [ 22 ] Patient compliance is an important factor affecting the quality of colonoscopy. [ 23 , 24 ] Educational interventions significantly improve the patients’ bowel preparation quality.…”
Section: Discussionmentioning
confidence: 99%